Insects Associated With The Medicinally Important Plants Used By The Tai Khamyang Tribe Of Titabar, Assam - Dr. Pollobi Duara (Journal of Advanced Zoology, 2024)
A small, very small Assamese community group known as the Tai Khamyang or Shyam people live in the districts of Tinsukia, Jorhat, Sivasagar, and Golaghat in Assam, as well as certain nearby areas of Arunachal Pradesh. The villages where the Shyam people live, Balijaan Shyam Gaon, Na Shyam Gaon, and Betbari Shyam Gaon in Titabor in the Jorhat district, were chosen for the research. The people of rural areas are mostly economically unstable and dependent on medicines extracted from plants for the treatment of diseases, as it has almost no side effect. The curing capacity of the medicinal plants is also good. The survey was done to collect data by interaction with the local people and interviews were taken with the people of the area to get an idea about their food habits and uses of medicinal plants. Several new findings on traditional rural practices were reported. A total of 43 species of flower-visiting insects were reported associated with 26 species of medicinally important flowering plants used by the Shyam people. The flower-visiting insects unintentionally transfer the pollen grains from the anther to the stigma while nectaring, thus helping in pollination. The insects visit the flowering plants for nectaring.